Effects of Cryogenic Treatment and Tempering on Mechanical Properties and Microstructure of 0.25C-0.80Si-1.6Mn Steel - Yuhua Li; Yongli Chen; Xuejiao Zhou (Advances in Materials Science and Engineering, 2020)
The effects of mechanical strength and yield ratio on the seismic steel are significant. This paper investigated the mechanical strength and yield ratio of medium carbon seismic steel by deep cryogenic treatment at −60°C and −110°C for 60∼120 s and tempering at 350°C for 30 minutes. The microstructure, misorientation, grain boundary, and size were characterized by electron backscattering diffraction (EBSD), scanning electron microscopy (SEM), and energy dispersive spectrometery (EDS). The result shows that the tensile strength and reduction of the cross-sectional area of steel were increased by 170 MPa and 9% and yield ratio and elongation were decreased by 0.13 and 9% due to the existence of the large-angle grain boundary. The present study confirms that the mechanical properties of medium seismic steel can be improved effectively by the deep cryogenic treatment and tempering.